2014
DOI: 10.1016/j.jccase.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Two-week administration of rivaroxaban resolved left atrial thrombus

Abstract: The incidence of nonvalvular atrial fibrillation increases with age, and left atrial thrombus complicated with nonvalvular atrial fibrillation is the major direct cause of cardiogenic thromboembolism that we need to prevent. Intravenous heparin and oral vitamin-K antagonist warfarin have been the most popular and the most frequently used agents for the treatment of left atrial thrombus in patients with atrial fibrillation [1]. Recently, novel oral anticoagulants such as a direct thrombin inhibitor dabigatran o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The therapy with Rivaroxaban was safe and clinical improvement was noted. There are a few published cases of left atrial ball thrombus successfully treated with oral anticoagulation [8,11]. Decision to remove the cardiac mass by surgical way, instead of the medical management with oral anticoagulation, could expose the patient to an unnecessary surgical risk.…”
Section: Discussionmentioning
confidence: 99%
“…The therapy with Rivaroxaban was safe and clinical improvement was noted. There are a few published cases of left atrial ball thrombus successfully treated with oral anticoagulation [8,11]. Decision to remove the cardiac mass by surgical way, instead of the medical management with oral anticoagulation, could expose the patient to an unnecessary surgical risk.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Besides its primary action of anticoagulation, its contribution to thrombolysis is postulated to be the inhibition of thrombus extension, which in turn causes unstable fibrin networks to be broken down by plasmin. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…Of those that did, Kaku 10 described that dabigatran induced endogenous fibrinolysis, while Nagamoto et al 11 reported dabigatran had thrombolytic action on acute preexisting intracardiac thrombus. Regarding rivaroxaban, Kato et al 12 presumed that there was promotion of fibrinolysis due to a peak and trough period, and Takasugi et al 14 reported that rivaroxaban caused a looser clot to form that is more sensitive to fibrinolytic enzyme by decreasing thrombin production. In our case, we speculate that a new thrombus formed on the unstable plaque that was originally present at the site of onset in the right internal carotid artery when oral intake of dabigatran was insufficient, and after admission, oral intake of dabigatran became regular and there was resolution of the new thrombus by a mechanism similar to that of resolution of intracardiac thrombus in previous reports.…”
Section: Discussionmentioning
confidence: 99%